2018
DOI: 10.1080/1478422x.2018.1459064
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behaviour of Super 304H stainless steel in supercritical water

Abstract: Oxidation of Super 304H steel in supercritical water at 600°C and 25 MPa was investigated, for the oxidation time of up to 1000 h. The oxidation kinetics approximately followed a parabolic law. The composition and microstructure of the oxide were investigated using the SEM equipped with EDS, EBSD and XRD. The phase compositions of the oxide evolve with increasing time. Cr 2 O 3 was present at the initial stage and not detected while Fe 2 O 3 appeared at longer time. EBSD indicated that continuous Cr 2 O 3 form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Indeed, within the shown grain (Figure 11), metallic un-oxidised zones can still be observed inside the grain. Lath preferential oxidation was also observed by Bischoff and coworkers on ferritic steels [31] and similar microstructures were observed by Li [8] Yang [19] and Tepylo [26] and coworkers on 304 H stainless steel and by Zhu et al on TP347HFG stainless steel [32] after steam oxidation. In agreement with Chen and coworkers' findings [11], the formation of Cr-rich layers in this inner oxide leads to Cr depletion and indeed, on the areas surrounding the nodules, Cr depletion can be observed on the element map showed in Figure 9.…”
Section: Microstructure Of the Oxide Scales Developed Under Atmospheric Steamsupporting
confidence: 81%
See 2 more Smart Citations
“…Indeed, within the shown grain (Figure 11), metallic un-oxidised zones can still be observed inside the grain. Lath preferential oxidation was also observed by Bischoff and coworkers on ferritic steels [31] and similar microstructures were observed by Li [8] Yang [19] and Tepylo [26] and coworkers on 304 H stainless steel and by Zhu et al on TP347HFG stainless steel [32] after steam oxidation. In agreement with Chen and coworkers' findings [11], the formation of Cr-rich layers in this inner oxide leads to Cr depletion and indeed, on the areas surrounding the nodules, Cr depletion can be observed on the element map showed in Figure 9.…”
Section: Microstructure Of the Oxide Scales Developed Under Atmospheric Steamsupporting
confidence: 81%
“…This was also proposed by Yang and coworkers to form on 304H after 1000 h under flowing steam at 650 °C [19], and by Li et al when exposing SS310 to supercritical (29 MPa) steam at 625 °C [6]. The lower Cr content of the outer zone of the scale may be caused by Cr evaporation as proposed by other authors [8]. Under this scale a Cr depletion substrate zone was observed, with only 10.5 wt.% Cr as opposed to 18 wt.% in the bulk alloy.…”
Section: Microstructure Of the Oxide Scales Developed Under Atmospheric Steamsupporting
confidence: 59%
See 1 more Smart Citation
“…Although the alloy with a high Cr content tends to form a dense, continuous, and protective Cr 2 O 3 layer than does the alloy with a low Cr content, the optimum Cr content is approximately 20 wt % commonly. , However, Cr 2 O 3 can evaporate in the forms of CrO 3 , CrO 2 (OH), and especially CrO 2 (OH) 2 in SCW with a high oxygen content . More specifically, Cr 2 O 3 and CrO 3 can react with water and oxygen to form an oxide hydroxide (i.e., CrO 2 (OH) 2 (chromium­(VI)) by reactions ,,,,,,, and . CrO 2 (OH) 2 is an active volatile species and probably formed in the metal wastage process in high-temperature and high-pressure water on the oxide/substrate interface .…”
Section: Reactions Of Typical Elementsmentioning
confidence: 99%
“…Therfore, it has been a promising candidate material for fuel cladding in SCWR [3]. Its corrosion behavior in SCW and water vapor has been widely studied [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Previous results showed that 304 stainless steel has good corrosion resistance in SCW under 550 ºC, however, a substantial increase of corrosion rate appeard above this temperature.…”
Section: Introductionmentioning
confidence: 99%